2004
DOI: 10.1074/jbc.m405366200
|View full text |Cite
|
Sign up to set email alerts
|

Paramecium bursaria Chlorella Virus-1 Encodes an Unusual Arginine Decarboxylase That Is a Close Homolog of Eukaryotic Ornithine Decarboxylases

Abstract: Paramecium bursaria chlorella virus (PBCV-1) is a large double-stranded DNA virus that infects chlorellalike green algae. The virus encodes a homolog of eukaryotic ornithine decarboxylase (ODC) that was previously demonstrated to be capable of decarboxylating L-ornithine. However, the active site of this enzyme contains a key amino acid substitution (Glu for Asp) of a residue that interacts with the ␦-amino group of ornithine analogs in the x-ray structures of ODC. To determine whether this active-site change … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
45
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

6
3

Authors

Journals

citations
Cited by 31 publications
(46 citation statements)
references
References 52 publications
0
45
1
Order By: Relevance
“…P. bursaria Chlorella virus-1 (PCBV-1) has a 331-kbp genome) that infect single-celled eukaryotes such as the green alga Chlorella, an endosymbiont of the ciliate P. bursaria. The presence of hss in the chloroviral genomes is intriguing because these genomes also contain a biosynthetic pathway consisting of an unusual arginine decarboxylase (58), an agmatine deiminase and N-carbamoylputrescine amidohydrolase (59), that together produce putrescine from arginine. An HSS orthologue from PCBV-1 was shown previously to be functional, producing homospermidine from two molecules of putrescine (39).…”
Section: Resultsmentioning
confidence: 99%
“…P. bursaria Chlorella virus-1 (PCBV-1) has a 331-kbp genome) that infect single-celled eukaryotes such as the green alga Chlorella, an endosymbiont of the ciliate P. bursaria. The presence of hss in the chloroviral genomes is intriguing because these genomes also contain a biosynthetic pathway consisting of an unusual arginine decarboxylase (58), an agmatine deiminase and N-carbamoylputrescine amidohydrolase (59), that together produce putrescine from arginine. An HSS orthologue from PCBV-1 was shown previously to be functional, producing homospermidine from two molecules of putrescine (39).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, although it was suggested that arginine decarboxylation reaction in the rodent brain may be catalyzed by ODC (49), later studies reported that rat ADC was able to decarboxylate both arginine and ornithine, this enzyme being distinct from ODC (44). In this regard, a viral gene, a close homologue of eukaryotic ODC, has been shown to code for an enzyme capable of decarboxylating L-arginine preferentially to L-ornithine (50). Recently, Regunathan and co-workers (51) have identified a human cDNA clone that exhibits ADC activity when expressed in COS-7 cells.…”
mentioning
confidence: 99%
“…However, the four polyamines detected in the PBCV-1 virion (putrescine, cadaverine, spermidine, and homospermidine) are unlikely to be important in neutralizing its DNA because the number of polyamine molecules per virion could neutralize only ϳ0.2% of the DNA phosphate residues (5). Presumably, polyamines play an essential role in the PBCV-1 replication cycle because PBCV-1 encodes four functional polyamine biosynthetic enzymes, arginine/ornithine decarboxylase, agmatine iminohydrolase, N-carbamoylputrescine amidohydrolase, and homospermidine synthase (HSS) (5,6,27). The first three enzymes can convert arginine to putrescine, which is an important intermediate in the synthesis of spermidine, spermine, and homospermidine (supplemental Fig.…”
Section: Resultsmentioning
confidence: 99%